ASSESSMENT OF ADVERSE DRUG REACTIONS OF ANTIDEPRESSANT DRUGS USED IN PSYCHIATRY DEPARTMENT OF A TERTIARY CARE HOSPITAL - KUSHWAHA, VIRENDRA; AGRAWAL, POOJA; SINGH, SARITA; CHAUDHARY, DHANANJAY; VERMA, AMIT K.; SHARMA, HIMANSHU (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The aim of the study was to analyze adverse drug reactions (ADRs) reported in patients prescribed antidepressants at tertiary care hospital. Methods: A prospective and observational study was conducted during January 2020–July 2021 at Department of Pharmacology in collaboration with the Department of Psychiatry, GSVM Medical College, and Kanpur. All patients diagnosed with depression and receiving pharmacotherapy were included in the study. ADRs were monitored using the standard form of the Central Drugs Standard Control Organization and causality was determined using the Naranjo algorithm. Data were evaluated for patient’s demography, risk factors for ADRs, and pattern of ADR. Results: A total of 293 ADRs were recorded from 110 patients. The most common ADRs observed were anxiety (47.42%) and insomnia (19.22%). Men (58.18%) were most commonly affected than women (41.82%). The most common causal drugs among antidepressants were Escitalopram (27.27%) and Venlafaxine (21.81%), respectively. The most common system involved was central nervous system (53.24%) followed by gastrointestinal system (41.63%). The majority of ADRs (97.95%) were possible according to the Naranjo’s scale. Conclusion: Anxiety, insomnia, and dizziness were the common ADRs which were associated with the use of antidepressants. This study offers a representative profile of the ADRs which can be expected in the psychiatry outpatients.